Histologic Evaluation of New Doxycycline Gel Formulation for Subgingival Application in Experimental Periodontitis in Rats - Ali Mohammad Tamaddon; Faezeh Saadati; Hengameh Khosropanah; Ali Dehghani Nazhvani; Gholam Hossein Yousefi (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2020)
Background and aim: Adjunctive therapy can increase periodontal treatments' success, and to date, various drugs had been suggested. This study aimed to test the efficacy of a new formulation of locally delivered- slow-releasing 10% doxycycline (DOX) gel as a thermogelating system by histologic evaluation in rats with experimental periodontitis. Materials and methods: Periodontal disease was induced with a ligature in maxillary left and right upper first molars of twenty male Sprague-Dawley rats in a seven-day duration. Left molars were treated with DOX gel while the right ones received vehicle drug in the subgingival area. Animals were randomly divided into two groups (each group contained ten rats). One group received the drug only once, while the second one was treated with twice the drug's application. After seven days, animals were killed and prepared for histologic evaluation. Results: Application of DOX gel reduced the degree of inflammation, presence of osteoclasts and resorptive lacuna, and the amount of disorientated collagen fibres after one week compared to teeth treated with vehicle drug (p <0.05) after twice application of the drug no adverse effect and necrotic changes were detected in histologic evaluations. Conclusion: This novel formulation of DOX gel is an effective and safe drug for treating periodontal disease in rats. It seems that the drug can be tested in human clinical trials as an adjunctive treatment for periodontal disease.